Pemahaman Percakapan Bahasa Asing Bagi Pemandu Wisata Di Kawasan Wisata Kampung Aur - M Mayasari; Wan Anayati; Muhizar Muchtar; H Hidayati; Muhammad Kiki Wardana (Jurnal TUNAS, 2022)
Community service activities in understanding foreign language conversation skills especially English for tour guides are seen as an effective and selective activity in improving the ability of tour guides to use English. The method used in this community service activity is a simulation method using lecture models, role playing and picture and picture which are used to provide explanations about making conversations in English appropriately and motivating tour guides to have a willingness to improve their English skills and increase understanding the tour guides regarding making conversations in English. The Question-and-Answer method is also used to determine the ability of the tour guides to receive explanations. The Simulation method is used so that the tour guides can practice the material that has been received. The stages in this simulation are the preparation stage, the simulation implementation stage, namely, the preparation for the simulation implementation. At this stage, an explanation was given regarding making conversations in English which focused on (1) The application of the picture and picture learning model in the simulation improves English conversation skills for tour guides. (2) the application of the role playing model in the simulation improves the English conversation skills of the tour guides. To see the ability of the tour guides, it can be proven by the acquisition of pretest and posttest scores and the ability of the tour guides to practice conversation in English properly.